Air quality of Prague: traffic as a main pollution source - Branis, Martin (Environmental monitoring and assessment, 2009)
Political and economical transition in the Central and Eastern Europe at the end of eighties significantly influenced all aspects of life as well as technological infrastructure. Collapse of outdated energy demanding industry and adoption of environmental legislation resulted in seeming improvements of urban environmental quality. Hand in hand with modernization the newly adopted regulations also helped to phase out low quality coal frequently used for domestic heating. However, at the same time, the number of vehicles registered in the city increased. The two processes interestingly acted as parallel but antagonistic forces. To interpret the trends in urban air quality of Prague, Czech capital, monthly averages of PM(10), SO(2), NO(2), NO, O(3) and CO concentrations from the national network of automated monitoring stations were analyzed together with long term trends in fuel consumption and number of vehicles registered in Prague within a period of 1992-2005. The results showed that concentrations of SO(2) (a pollutant strongly related to fossil fuel burning) dropped significantly during the period of concern. Similarly NO(X) and PM(10) concentrations decreased significantly in the first half of the nineties (as a result of solid fuel use drop), but remained rather stable or increased after 2000, presumably reflecting rapid increase of traffic density. In conclusion, infrastructural changes in early nineties had a strong positive effect on Prague air quality namely in the first half of the period studied, nevertheless, the current trend in concentrations of automotive exhaust related pollutants (such as PM(10), NO(X)) needs adoption of stricter measures.
Keywords: ozon; výfukové emise vozidel; oxid uhelnatý; monitorování životního prostředí; oxid siřičitý; Ozone; Vehicle Emissions; Particulate Matter; Air Pollutants; Czech Republic; Environmental Monitoring; oxid dusičitý; Nitrogen Dioxide; Česká republika; oxid dusnatý; látky znečišťující vzduch; Carbon Monoxide; Nitric Oxide; Sulfur Dioxide; pevné částice